Implementation of Electronic Fiscal Tools (EFD) in Increasing Restaurant Taxpayer Compliance and Restaurant Tax Revenue in Bandung City - Asri Banyu Pertiwi; Aceng Kurniawan (Jurnal Riset Perpajakan: Amnesty, 2024)
This research is motivated by various problems related to the implementation of Electronic Fiscal Tools, including network problems. This research aims to determine the extent to which the implementation of the Electronic Fiscal Tool (EFD) has increased restaurant taxpayer compliance and restaurant tax revenue in the city of Bandung. The theory used to measure taxpayer compliance is Nurmantu's theory, while to measure effectiveness the theory of Minister of Home Affairs Decree Number 690,900,327 of 1996 is used. Researchers use a case study approach, which is a type of qualitative research, as an important part of the research process. The object of this research was carried out at the Bandung City Regional Revenue Agency Office and the restaurant taxpayer's place. In collecting data, researchers use primary and secondary data such as interviews, observation and documentation. The results show that in the implementation process of the Implementation of Electronic Fiscal Tools (EFD) in Increasing Restaurant Taxpayer Compliance and Restaurant Tax Revenue in the City of Bandung it can be said to be quite optimal. Although there are still many shortcomings or obstacles faced by the Bandung City Bapenda in the first year of using the Electronic Fiscal Tool (EFD)